Association between IL12A Gene of G/A genotype Polymorphism and Pulmonary Tuberculosis Risk in Baghdad Population - Anwar Abed Nasser Dhabaan1, Mayes Abdul-Hadi Mahdi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study included eighty samples. This cases-controlled study was performed including fifty Pulmonary tuberculosis patients, their ages ranged from 12 to 77 year (27 female and 23 male) and thirty controls (healthy), their ages ranged from 19 to 58 year (15 female and 15 male). We confined the frequency of IL12A gene (G/A rs568408 genotype) polymorphism by Tetra-ARMS PCR (Tetra amplification refractory mutation system-polymerase chain reaction) technology. Also, we determined the association of IL12A Gene (G/A rs568408 genotype) polymorphism with Pulmonary tuberculosis patients in Baghdad. Statistical results showed significant difference in genotype frequency of IL12A Gene (G/A rs568408 genotype) polymorphism between Pulmonary tuberculosis patients and control (healthy). The G allele shows high frequency in Pulmonary tuberculosis patients comparison with control (healthy) and present related with etiological fraction risk of Pulmonary tuberculosis patients and its ratio 62% in patients and 51.67% in control (healthy), While A allele shows high frequency in control (healthy) comparison with Pulmonary tuberculosis patients and present related with protective fraction of Pulmonary tuberculosis patients and its ratio 48.33% in control and 38% in Pulmonary tuberculosis patients. The genotypes of GG and AA homozygotes shows high frequency in Pulmonary tuberculosis patients comparison with control (healthy), and its ratio 42% and 18% respectively in Pulmonary tuberculosis patients, while its ratio 3.33% and 0% respectively in control (healthy), also GG and AA genotypes appear related with etiological fraction risk of Pulmonary tuberculosis patients, while the GA heterozygote show high frequency in control (healthy) and its ratio 96%, GA genotypes related with preventive fraction of Pulmonary tuberculosis patients. Our findings demonstrate that the IL12A Gene (G/A rs568408 genotype) polymorphism may represent a significant risk factor for pulmonary tuberculosis patients in Baghdad population.